Initiation, Adherence, and Retention in a Randomized Controlled Trial of Directly Administered Antiretroviral Therapy - Maru, Duncan Smith-Rohrberg (2007)
Directly administered antiretroviral therapy (DAART) can improve health outcomes among HIV-infected drug users. An understanding of the utilization of DAART—initiation, adherence, and retention—is critical to successful program design. Here, we use the Behavioral Model to assess the enabling, predisposing, and need factors impacting adherence in our randomized, controlled trial of DAART versus self-administered therapy (SAT) among 141 HIV-infected drug users. Of 88 participants randomized to DAART, 74 (84%) initiated treatment, and 51 (69%) of those who initiated were retained in the program throughout the entire six-month period. Mean adherence to directly observed visits was 73%, and the mean overall composite adherence score was 77%. These results were seen despite the finding that 75% of participants indicated that they would prefer to take their own medications. Major causes of DAART discontinuation included hospitalization, incarceration, and entry into drug-treatment programs. The presence of depression and the lack of willingness to travel greater than four blocks to receive DAART predicted time-to-discontinuation.